Impact of Fieldtrip and Demonstration Instructional Strategies on Senior Secondary School Students’ Achievement and Retention on Concept of Pollution in Biology, Minna, Niger State, Nigeria - Babagana. M.; Yaki. A. A.; Abubakar Zainab (International Journal on Integrated Education, 2022)
This study examines the Impact of Demonstration and Fieldtrip Instructional Strategies on Senior Secondary School Biology Student’s Achievement and Retention in Edati Local Government Area of Niger State. A pre-test post-test control quasi experimental design was adopted for the study. A total of 105 (49 males and 56 females) senior secondary school I (SSI) students drawn from two (2) Senior Secondary Schools were used for the study. The students were randomly assigned to Experimental and Control Groups. Six (6) hypotheses were formulated and tested at 0.05 level of significance. The instrument used for data collection was the Biology Achievement Test (BAT) consisting of 20 multiple choice items which was developed by the researcher and validated by the experts in the field. A reliability coefficient of 0.85 was obtained using Cronbach alpha analysis and data collected were analysed. The result indicates that there was a significant difference in the mean achievement scores of students taught using Fieldtrip method and those taught using Demonstration method (t = 6.504, df = 103, p<0.05), there was a significant difference in the mean achievement scores of male and female students taught using Fieldtrip method with (t = 5.129, df = 56, p<0.05), there was a significant difference in the mean achievement scores of male and female students taught using Demonstration method with (t = 4.531, df = 45 p<0.05), there was a significant difference in the mean retention scores of students using Fieldtrip method and those taught using Demonstration method with (t = 3.852, df = 103, p<0.05), there was also a significant difference in the mean retention scores of male and female students taught with the use of Fieldtrip method with (t = 3.522, df = 56, p<0.05) and there was a significant difference in the mean retention scores of male and female students taught using Demonstration method with (t = 2.401, df = 45, p<0.05). Based on these findings, it was concluded that the use of Fieldtrip method is more effective in improving student’s achievement in Biology than the use of Demonstration method. It is therefore recommended that School authority together with the school principal should encourage and give necessary support to teachers to provide and create avenue for students to embark on Fieldtrip activities for effective teaching and learning of Biology in secondary schools.